A homogenization approach for the limit analysis of out-of-plane loaded masonry walls - Milani, G. (2006)
This paper addresses the usage of a simplified homogenization technique for the analysis of masonry subjected to out-of-plane loading. The anisotropic failure surface, based on the definition of a polynomial representation of the stress tensor components in a finite number of sub-domains, is combined with finite element triangular elements employed for the upper and lower bound limit analyses. Several comparisons between the proposed model and experimental data available in the literature are presented, for wallettes subjected to bending at different orientations and for different panels loaded out-of-plane. The limit analysis results allow to identify the distribution of internal forces at critical sections and to obtain the collapse modes, as well as the failure loads. Excellent results are found in all cases, indicating that the proposed simple tool is adequate for the safety assessment of out-of-plane loaded masonry panels. The combined usage of upper and lower bound approaches, and their respective simplifications, allow to define a narrow interval for the real collapse load.